School Choice and School Governance - Herbst, J. author. aut Link
XIII, 207 p.
Keywords: For over 200 years, legislators, educators, and public-minded citizens have debated how to govern public schools. This book reviews these debates and discusses racial integration, ethnicity, social class, vouchers, charter, magnet and private schools in the United States, the former German Democratic Republic and the Federal Republic of Germany.